The Influence of Brand Congruity on Brand Evangelism through the Mediation of Brand Trust and Brand Commitment among Generation Z Shopee Users - Hari, Abdul Hadi; Sabardini, Sri Ekanti (Telaah Bisnis, 2025)
This study aims to analyse the influence of brand congruity on brand evangelism by examining the mediating roles of brand trust and brand commitment among Generation Z Shopee users. Brand congruity refers to the alignment between a consumer’s self-image and the brand image, which plays a crucial role in shaping high-level consumer engagement in digital marketing contexts. This research adopts a quantitative approach utilizing Partial Least Squares Structural Equation Modelling (PLS-SEM) for data analysis. Data were collected through questionnaires distributed to 145 Generation Z respondents who are active Shopee users. The findings reveal that brand congruity has a direct and significant effect on brand evangelism, as well as an indirect effect through brand trust and brand commitment as partial mediators. The mediation pathways suggest that trust and commitment toward the brand serve as critical psychological mechanisms bridging identity congruence and brand advocacy behavior. These findings underscore the importance for companies to develop brand images that resonate with consumer values and identities, while also strengthening trust and emotional attachment to drive brand evangelism behavior.